2014
DOI: 10.1016/j.jgr.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of cultivation ages and cultivars of ginseng leaves using Fourier transform infrared spectroscopy combined with multivariate analysis

Abstract: To determine whether Fourier transform (FT)-IR spectral analysis combined with multivariate analysis of whole-cell extracts from ginseng leaves can be applied as a high-throughput discrimination system of cultivation ages and cultivars, a total of total 480 leaf samples belonging to 12 categories corresponding to four different cultivars (Yunpung, Kumpung, Chunpung, and an open-pollinated variety) and three different cultivation ages (1 yr, 2 yr, and 3 yr) were subjected to FT-IR. The spectral data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 50 publications
1
17
0
4
Order By: Relevance
“…특히 FT-IR을 이용한 분석법은 높은 감도를 가지며 다수의 시료로부터 얻어진 스펙트럼을 쉽고 간편하게 조사할 수 있는 장점을 가지고 있다. 최근 FT-IR 스 펙트럼 데이터의 다변량 통계분석 기술은 유연관계가 높은 고등식물의 종 구분 (Kwon et al 2011;Kim et al 2007) 및 품종 식별 (Kwon et al 2014…”
unclassified
“…특히 FT-IR을 이용한 분석법은 높은 감도를 가지며 다수의 시료로부터 얻어진 스펙트럼을 쉽고 간편하게 조사할 수 있는 장점을 가지고 있다. 최근 FT-IR 스 펙트럼 데이터의 다변량 통계분석 기술은 유연관계가 높은 고등식물의 종 구분 (Kwon et al 2011;Kim et al 2007) 및 품종 식별 (Kwon et al 2014…”
unclassified
“…Genotype, ginsenoside contents and phenotypes were different in different ginseng cultivars (Kwon et al, ; Lee, Park, Lee, Jayakodi, Kim, Koo, et al, ; Lee, Park, Lee, Jayakodi, Kim, Lee, et al, ; Sun et al, ). Tissue culture is a stress state for plants due to the lack of suitable nutrients for growth or high concentrations of growth regulators (e.g., auxin), and the differences among cultivars mainly represent the unique characteristics under a strictly controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…Different ginseng cultivars have different phenotypes [4], genetic polymorphisms [3], [5], [6], and ginsenoside contents [7], [8], [9]. Many previous studies have revealed genetic and metabolic diversities based on DNA polymorphisms and metabolite profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity among cultivars has been revealed by simple sequence repeat [3], single nucleotide polymorphism [5], and sequence characterized amplified region marker [6] analyses based on DNA polymorphisms. The metabolic diversity of ginseng cultivars has been investigated via HPLC [7], Fourier transform infrared [8], and nuclear magnetic resonance [9] analyses. However, to date, only a few studies have been performed on the diversity of primary metabolites in ginseng cultivars [9].…”
Section: Introductionmentioning
confidence: 99%